A case of aortic dissection in familial Mediterranean fever. Issue 6 (December 2021) - Malik, Asmara; Malik, Jahanzeb; Javaid, Muhammad; Khan, Hamid Sharif; Mohsin, Muhammad; Shoaib, Muhammad
Abstract: Familial Mediterranean fever (FMF) is an ethnicity-specific autoinflammatory disease prevalent in the Arab world. It has various presentations including amyloidosis, small-vessel vasculitis, and pericarditis. Different mutations in the Mediterranean fever (MEFV) gene can cause this disorder and it is inherited in an autosomal recessive pattern. We present a case of a 23-year-old man of Iranian descent with history of periodic fever, diagnosed as Stanford type A aortic dissection secondary to an acute attack of FMF. To the best of our knowledge, this is the first case reported of such a complication. <Learning objective: 1. Diagnosis of familial Mediterranean fever is a diagnosis of exclusion as many diseases involve large arteries and present with aortic involvement. 2. Familial Mediterranean fever usually involves small- and medium-sized arteries but unusual case presentations can occur in some patients involving the aorta. 3. Physicians in Pakistan must be made aware of the rapidly increasing prevalence of familial Mediterranean fever due to migration of susceptible ethnic groups in order to manage patients while they are still amenable to treatment.>